(t,k)-diagnosability of exchanged crossed cube under the PMC model - Chen GUO; Zhifang XIAO; Ming LEMG; Shuo PENG; Bo WANG (Tongxin xuebao)
Exchanged crossed cube(ECQ) is one of the latest achievements in the research of topology of novel interconnection networks.ECQ is a more optimized form of organization for multi-processor parallel computers,which retains the advantages of exchanged hypercube and crossed cube in terms of the smaller diameter,fewer links,and lower cost factor,and which indicates more balanced consideration.However,so far,ECQ hadn’t been formally introduced into multi-processor parallel computers.One of the main reasons was that its reliability research wasn’t yet systematic.Among them,the operational reliability represented by diagnosability was the most urgent.ECQ was taken as studying object,after topological analyzing,some important topological properties of ECQ were introduced,which determines the (t,k)-diagnosability of ECQ(s,t) under the PMC model by theoretical deduction and simulation experiments.Simulation results show that ECQ reliability complement and improvement,which provides strong technical support for subsequent application and popularization.